2022
DOI: 10.1371/journal.pone.0277167
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the KOJI AWARENESS self-screening test for body movement and comparison with functional movement screening

Abstract: Objective This study aimed to validate the KOJI AWARENESS™, a self-screening movement test, and compare it with the Functional Movement Screen (FMS). Methods Fifty-seven healthy participants completed the KOJI AWARENESS™ and functional movement screening. Pearson’s correlation coefficients were used to assess the validity of the test. Subsequently, partial correlation analysis was used to determine the associations between age, sex, body mass index, and sports level as control variables and motor function. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The Koji Awareness screening test is fundamentally designed to screen motor function in a holistic and composite manner [6]. Our previous research confirmed that the KOJI AWARENESS TM is a valid test that correlates strongly and positively with scores on the Functional Screening Test (FMS), a well-known screening test for motor function [7]. The FMS can be used to predict injury and has been demonstrated to have adequate reliability and validity in systematic reviews [810].…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…The Koji Awareness screening test is fundamentally designed to screen motor function in a holistic and composite manner [6]. Our previous research confirmed that the KOJI AWARENESS TM is a valid test that correlates strongly and positively with scores on the Functional Screening Test (FMS), a well-known screening test for motor function [7]. The FMS can be used to predict injury and has been demonstrated to have adequate reliability and validity in systematic reviews [810].…”
Section: Introductionmentioning
confidence: 79%
“…The KOJI AWARENESS TM is composed of measures of ROM, muscle strength, and balance [7]. Further details on KOJI AWARENESS™ are provided in Appendices 1 and 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects assess the criteria by themselves, using their own bodies. Murofushi et al (20) reported that analysis of the relationship between KOJI AWARENESS™ score and FMS score showed a strong positive correlation (r = 0.576, p < 0.001). They also reported that the KOJI AWARENESS™ score of athletes showed a significant negative correlation (r = -0.507) with the degree of pain, even when age, body mass index (BMI), gender, and other variables were used as control variables (19).…”
Section: Introductionmentioning
confidence: 99%